Haemophagocytic syndrome complicating acute lymphoblastic leukaemia. Issue 762 (April 1989) - Stark, R.; Manoharan, A.
Abstract : A 41 year old female developed reactive haemophagocytic histiocytosis secondary to herpes simplex infection, during remission induction for acute lymphoblastic leukaemia. She recovered fully with acyclovir and supportive treatment. Previous publications on the association between acute lymphoblastic leukaemia and haemophagocytic syndrome are reviewed, and the nature of the haemophagocytic disorder is discussed.